Internalizing the Character Value of Caring for the Environment Through the Project to Strengthen the Profile of Pancasila Students in Elementary Schools - Rhindra Puspitasari; Dasim Budimansyah; Sapriya Sapriya; Rahmat Rahmat (IJORER : International Journal of Recent Educational Research, 2023)
Objective: Finding appropriate ways to internalize the character values ​​of caring for the environment in elementary schools through a project to strengthen the profile of Pancasila students in terms of civic behavior, skills, and attitude. Method: This research is mixed research with quasi-experiment, with a population of 500 students from 5 elementary schools and a sample of 128 students from 3 elementary schools. Results: The internalization of environmentally caring character values ​​carried out through the project to strengthen the Pancasila student profile in elementary school students is quite effective with the final score of the experimental class; Elementary School 1 Jampiroso scored 82.0% civic behavior, civic skill 80% and civic attitude 81.0%, while Elementary School 2 Jampiroso scored civic behavior 81.0%, civic skill 80.0% and civic attitude 80.0% and Elementary School Shekinah civic behavior 83.0%, civic skill 80.0% and civic attitude 82.0%. Novelty: This research is a study of further experimental development related to the development of civic behavior, skills, and attitudes in elementary schools